Multi-Agent Competition Simulation of Integrated Transportation System - Jiashun Zhang; Rongjie Lv (Institute of Advanced Engineering and Science, 2013)
Transportation networks have been developed during the recent decades with the rapid growth of economy. At the same time, the conflicts between different transportation modes were getting more and more intense. To describe the competition relationship in integrated transportation system, a multi-agent competition model was presented. It is important to provide decision support for regulators to lead more reasonable distribution of resources for planning and operating the integrated transportation network. Thus, a simulation program was developed to implement the proposed model and provide computer-aid decision support. Finally, several experiments were conducted to illustrate the effectiveness of this technique. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1906